Clinical investigation of 38 cases of oral mucosal melanoma: A multicentre retrospective analysis in Japan. (15th August 2017) - Yamada, Shin‐ichi; Kurita, Hiroshi; Kamata, Takahiro; Kirita, Tadaaki; Ueda, Michihiro; Yamashita, Tetsuro; Ota, Yoshihide; Otsuru, Mitsunobu; Yamakawa, Nobuhiro; Okura, Masaya; Aikawa, Tomonao; Yanamoto, Souichi; et al.
Abstract: Background/Objectives: The aim of the present study was to investigate treatment modalities and outcomes in oral mucosal melanoma. Methods: The clinical and pathological data of 38 consecutive patients with oral mucosal melanoma were retrospectively analyzed. Patients' characteristics were analyzed and overall survival (OS) rates were calculated. Results: Sixteen patients had stage III (42%), 19 IVA (50%), and three had stage IVC (8%) disease. Among the therapeutic approaches used, 31 patients (82%) received radical therapy (surgery +/− chemotherapy). The 5‐year OS rate was 40%. Five‐year OS rates according to the clinical stage were 71% for stage III, 24% for stage IVA, and 0% for stage IVC. Five‐year OS rates according to therapeutic approaches were 52% in the radical therapy group and 0% in the palliative therapy and best supportive care groups. Conclusions: The results of this multicentre retrospective analysis of patients with oral mucosal melanoma suggest that radical therapy based on surgical treatments with complete surgical excision with clear margins leads to a better prognosis.